GAYA HIDUP DAN TEKANAN DARAH PADA USIA PRODUKTIF DI KALURAHAN DEMANGREJO - Rahmi, Safirina Aulia (Akademi Kebidanan Mulia Madani Yogyakarta, 2024)
Background: Yogyakarta Special Region (DIY) is a province that has a prevalence of hypertension above the national value. There are 11 provinces whose scores are above the national score. DIY is the 4th highest province of all provinces in Indonesia for the prevalence of hypertension. The aim of this study was to analyze the relationship between lifestyle (salt consumption, sugar consumption and physical activity) with the incidence of hypertension in productive age.. Methods: This research is an analytical type of research, with a cross sectional research design. The population was 30 residents who carried out screening during Posyandu activities in Demangrejo Village. The sample consisted of 30 respondents taken using total sampling technique. The statistical analysis used to determine the relationship between the independent and dependent variables is Chi-square. Results: The results of the study showed that there was no relationship between salt consumption (p=0.660), sugar consumption (p=0.603), and physical activity (p=1.000) on blood pressure in productive age in Demangrejo District. Conclusion: Most of the respondents in this study consumed > 4 tablespoons of sugar per day and most did not do physical activity. The results of statistical analysis in this study show that there is no relationship between salt consumption, sugar consumption and physical activity on the blood pressure of productive age respondents in Demangrejo District.. Keywords: Blood pressure, sugar consumption, salt consumption, physical activity